Domestic forests: a new paradigm for integrating local communities’ forestry into tropical forest science - Michon, G.; Foresta, H. de; Levang, P.; Verdeaux, F. (2007)
Despite a long history of confrontation between forest agencies and forest people, “indigenous” or “local” practices are increasingly considered as a viable alternative of forest management. This paper is a synthesis derived from various long-term research programs carried out by the authors in Southeast Asia and Africa on forests managed by farmers. These researches looked at local practices and underlying science, including their social, political, and symbolic dimensions. They also addressed evolutionary trends and driving forces, as well as potential and limits for forest conservation and development, mitigation of deforestation, biodiversity conservation, and poverty alleviation in a context of global environmental, political, and social change. We discuss how forest management by local communities, contrary to the unified models of professional forest management, exhibits a high historical and geographical diversity. The analysis we draw from the various examples we studied reveals several invariants, which allows proposing the unifying paradigm of “domestic forest.” The first universal feature concerns the local managers themselves, who are, in their vast majority, farmers. Management practices range from local interventions in the forest ecosystem, to more intensive types of forest culture, and ultimately to permanent forest plantation. But in all cases, forest management is closely integrated with agriculture. The second universal feature concerns the conceptual continuity of planted forests with the natural forest, in matters of vegetation’s structure and composition as well as economic traits and ecosystem services. The resulting forest is uneven-aged, composed of several strata, harboring a large diversity of species, and producing a wide range of products, with timber seldom being the dominant one. The term “domestic forest” aims at highlighting the close relationship the domestication process establishes between a specific human group, including its elementary units, the “domestic units,” and the forest, transformed and managed to fulfill the needs of that group. The domestic forest paradigm calls for the integration into forest science of a new concept of land management in which production and conservation are compatible, and in which there is no choice to be made between people and nature. It does not aim at contesting the value of conventional forest science, but it proposes domestic forests as a new scientific domain, for the combined benefit of forest science and of forest people. It does not contest the value of conventional forest management models, but pushes towards more equitable relations between forest agencies and farmers managing forest resources on their own lands.